Introduction to prescriptive AI a primer for decision intelligence solutioning with Python - Kulkarni, Akshay (Apress, 2023)
Gain a working knowledge of prescriptive AI, its history, and its current and future trends. This book will help you evaluate different AI-driven predictive analytics techniques and help you incorporate decision intelligence into your business workflow through real-world examples. The book kicks off with an introduction to decision intelligence and provides insight into prescriptive AI and how it can be woven into various business strategies and frameworks. You'll then be introduced to different decision intelligence methodologies and how to implement them, along with advantages and limitations of each. Digging deeper, the authors then walk you through how to perform simulations and interpret the results. A full chapter is devoted to embedding decision intelligence processes and outcomes into your business workflow using various applications. The book concludes by exploring different cognitive biases humans are prone to, and how those biases can be eliminated by combining machine and human intelligence. Upon completing this book, you will understand prescriptive AI, tools, and techniques and will be ready to incorporate them into your business workflow. You will: Implement full-fledged decision intelligence applications using Python Leverage the tools, techniques, and methodologies for prescriptive AI Understand how prescriptive AI can be used in different domains through practical examples Interpret results and integrate them into your decision making.